Opstand adelt? De rechtvaardiging van het politieke verzet van de adel in de Vlaamse Opstand (1482-1492) - Jelle Haemers (BMGN: Low Countries Historical Review, 2008)
Can a Revolt be Ennobling? Justification of the Political Opposition of the Nobility during the Flemish Revolt (1482-1492) This article analyses the political ideas of the late mediaeval nobility. In 1491, Archduke Maximilian of Austria accused three noblemen, Louis of Bruges, Adolf of Cleves and his son Philip, of lese majesty. The pleas made by the above-mentioned noblemen in this particular case are used to reconstruct their political ideology. The three noblemen maintained that service to the sovereign was one the most noble virtues of a nobleman, but they also considered that this political service had to be reciprocal. Using customary law, judicial treatises and political practices, they argued that the sovereign was the keystone of the political order, as long as he obtained advice from the noblemen when setting out his policies. He was also not allowed to violate any laws, traditions or privileges. These ideas had a long history in mediaeval political thought, and they would continue to dominate sixteenth-century society.